Effect of Interferon-γ on the Basal and the TNFα-Stimulated Secretion of CXCL8 in Thyroid Cancer Cell Lines Bearing Either the RET/PTC Rearrangement Or the BRAF V600e Mutation. (31st July 2016) - Rotondi, Mario; Coperchini, Francesca; Awwad, Oriana; Pignatti, Patrizia; Di Buduo, Christian A.; Abbonante, Vittorio; Magri, Flavia; Balduini, Alessandra; Chiovato, Luca
Abstract : CXCL8 displays several tumor-promoting effects. Targeting and/or lowering CXCL8 concentrations within the tumor microenvironment would produce a therapeutic benefit. Aim of this study was to test the effect of IFN γ on the basal and TNF α -stimulated secretion of CXCL8 in TCP-1 and BCPAP thyroid cancer cell lines (harboring RET/PTC rearrangement and BRAF V600e mutation, resp.). Cells were incubated with IFN γ (1, 10, 100, and 1000 U/mL) alone or in combination with TNF- α (10 ng/mL) for 24 hours. CXCL8 and CXCL10 concentrations were measured in the cell supernatants. IFN γ inhibited in a dose-dependent and significant manner both the basal (ANOVA F : 22.759;p < 0.00001 ) and the TNF α -stimulated (ANOVA F : 15.309;p < 0.00001 ) CXCL8 secretions in BCPAP but not in TPC-1 cells (NS). On the other hand, IFN γ and IFN γ + TNF- α induced a significant secretion of CXCL10 in both BCPAP (p < 0.05 ) and TPC-1 (p < 0.05 ) cells. Transwell migration assay showed that (i) CXCL8 increased cell migration in both TPC-1 and BCPAP cells; (ii) IFN γ significantly reduced the migration only of BCPAP cells; and (iii) CXCL8 reverted the effect of IFN γ . These results constitute the first demonstration that IFN γ inhibits CXCL8 secretion and in turn the migration of a BRAF V600e mutated thyroid cell line.